Housing wealth and consumption during Covid-19 - Per Andersen; Pernille Valentin Borgensgaard; Andreas Kuchler; Bjørn Bjørnsson Meyer (Danmarks Nationalbank, 2023)
House prices increased considerably in Denmark during the pandemic, while consumption remained moderate. This memo explores the nature of the muted consumption response based on a unique data set with estimates of the value of almost all single- and multi-family houses in Denmark obtained from a machine learning model. We find that the marginal propensity to consume (MPC) out of changes in housing wealth was modest in the years leading up to the pandemic. In addition, the largest housing wealth gains during the pandemic occurred among household segments with relatively low MPCs, such as households living in large cities with sizeable liquid assets and low loan-tovalue ratios.
Keywords: 330; Privater Konsum; Immobilienpreis; Wohneigentum; Vermögen; Coronavirus; Dänemark